Impact of surgical weight loss on novel P‐wave‐related variables which are nominated as predictors of atrial arrhythmias. Issue 9 (4th August 2021) - Ibisoglu, Ersin; Boyraz, Bedrettin; Güneş, Saime Turgut; Savur, Ümeyir; Naki Tekin, Deniz Dilan; Erdoğan, Aslan; Özdenkaya, Yaşar; Erdoğan, Emrah; Çeğilli, Ercan; Olgun, Fatih Erkam; Güneş, Hacı Murat
Abstract: Background: Bariatric surgery has been associated with reduced cardiovascular mortality and morbidity in obese patients. In this study, we aimed to evaluate the alterations of novel P‐wave related atrial arrhythmia predictors in patients who achieved effective weight loss with bariatric surgery. Methods: The study included 58 patients who underwent bariatric surgery. We measured heart rate, PR, P wave (PW) max, PW min, Average P axis, P wave peak time (PWPT) in lead D2 and lead V1, terminal force in lead V1 (V1TF), and we estimated P wave dispersion (PWdis) interval both pre‐operation and 6 months after operation. Results: Heart rate, PR, PW max, PW min, PWdis, Average P axis, PWPTD2, PWPTV1 and V1TF values, which were close to the upper limit in the pre‐op period, showed statistically significant decreases at 6 months after the operation. The most prominent changes were observed in PW dis (51.15 ± 9.70 ms vs. 48.79 ± 9.50 ms, p  = .010), PWPTD2 (55.75 ± 6.91 ms vs. 50.59 ± 7.67 ms, p  < .001), PWPTV1 (54.10 ± 7.06 ms vs. 48.05 ± 7.64 ms, p  < .001) and V1TF (25 [43.1%] vs. 12 [20.7%], p  < .001). Conclusions: The results of our study indicated that bariatric surgery has positive effects on the regression of ECG parameters which are predictors of atrial arrhythmias, particularly atrial fibrillation (AF).